Fototopografia: The “Futures Past” of Surveying - von Brevern, Jan (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2011)
This article examines a particular problem in the early history of photographic land surveying: the unwavering desire to use photography to capture accurate topographical information for map-making, even in light of practical difficulties. It considers how both the practical survey work and the status of photography changed when, instead of the landscape itself, photographs were measured. Photography’s promise to simplify strenuous fieldwork was almost as old as photography itself—but in practice, it took decades of experimenting until the process was feasible.